Social integration of adolescents with chronic pain: a social network analysis. Issue 11 (19th November 2022) - Van Alboom, Maité; Elmer, Timon; Boersma, Katja; Forgeron, Paula; Baert, Fleur; Bracke, Piet; Goubert, Liesbet
Abstract : Supplemental Digital Content is Available in the Text. Examining the role of popularity, homophily, and relationship quality in social networks of adolescents with chronic pain using social network analysis. Abstract: Adolescents with chronic pain (ACP) often experience impairments in their social functioning. Little is known about the consequences of these impairments on peer relationships of ACP. This study applied social network analysis to examine whether adolescents with more pain problems are less popular (RQ1), adolescents with similar pain problems name each other more often as being part of the same peer group (RQ2), dyads with an adolescent experiencing more pain problems report less positive (eg, support) and more negative (eg, conflict) friendship qualities (RQ3), and positive and negative friendship qualities moderate the relationship between pain and emotional distress (RQ4). This study used data from the first wave of a longitudinal study (N = 2767) which followed up Swedish adolescents from 19 public schools. For RQ1-3, Multiple Regression Quadratic Assignment Procedure was applied. For RQ4, standard multilevel models with observations of adolescents nested within schools were estimated. Results showed that ACP were not less popular than adolescents without chronic pain. Second, ACP nominated each other more often as being part of the same peer group. Third, results regarding friendship quality showed that adolescents with more pain problems perceived the relationship with their friends as less positive (eg, support) and more negative (eg, conflict) than adolescents with less pain problems. Finally, positive and negative friendship qualities moderated the relationship between pain and emotional distress. This study contributes to the literature on the importance of peer relationships of ACP. Clinical implications and directions for future research are discussed.